2013
DOI: 10.1242/jcs.130161
|View full text |Cite
|
Sign up to set email alerts
|

Spire-1 a novel contributor of invadosome and associated invasive properties

Abstract: Cancer cells have an increased ability to squeeze through extracellular matrix gaps that they create by promoting proteolysis of its components. Major sites of degradation are specialized microdomains in the plasma membrane collectively named invadosomes where the Arp2/3 complex and formin proteins cooperate to spatiotemporally control actin nucleation and the folding of a dynamic Factin core. At invadosomes, proper coupling of exo-endocytosis allows polarized delivery of proteases that facilitate degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 62 publications
2
37
0
Order By: Relevance
“…To test the specificity of melanosome clustering in SPIRE1/2 and FMN1 deficient cells we generated adenoviruses that express human (hs) SPIRE1/2 (these are resistant to mouse-specific siRNA) and mouse FMN1 as fusions to the C-terminus of EGFP. Add-back experiments in SPIRE1/2 depleted melan-a and melan-f melanocytes using these vectors confirmed that melanosome clustering was due to depletion of the endogenous proteins ( Figure 1D Previous studies reported that the sequence of the conserved SB portion of SPIRE1 is similar to the Rab binding domain (RBD) of the Rab3/27 effector Rabphilin-3A, and more recently the C-terminus membrane binding (SB and FYVE) portion of SPIRE1 was found to interact with Rab3a in vitro 30,38 .…”
Section: Resultssupporting
confidence: 55%
“…To test the specificity of melanosome clustering in SPIRE1/2 and FMN1 deficient cells we generated adenoviruses that express human (hs) SPIRE1/2 (these are resistant to mouse-specific siRNA) and mouse FMN1 as fusions to the C-terminus of EGFP. Add-back experiments in SPIRE1/2 depleted melan-a and melan-f melanocytes using these vectors confirmed that melanosome clustering was due to depletion of the endogenous proteins ( Figure 1D Previous studies reported that the sequence of the conserved SB portion of SPIRE1 is similar to the Rab binding domain (RBD) of the Rab3/27 effector Rabphilin-3A, and more recently the C-terminus membrane binding (SB and FYVE) portion of SPIRE1 was found to interact with Rab3a in vitro 30,38 .…”
Section: Resultssupporting
confidence: 55%
“…12). Several actin nucleators are associated with the F-actin-rich core, such as the Arp2/3 complex and its nucleation-promoting factors (N-WASP/WASP and cortactin), 4,[13][14][15] formins, 16,17 or Spire 18 that drive F-actin polymerization. Many actin-binding proteins such as fascin, vinculin, or cofilin are also markers of these structures.…”
Section: Introductionmentioning
confidence: 99%
“…P4HA1 may also enhance invasion by regulating the expression of invasion‐associated genes, such as SPIRE1, which was downregulated, and DKK1, which was upregulated in the P4HA1‐knockdown cells. SPIRE1 is an actin nucleator, which is a part of the invadosome and promotes matrix degradation (Lagal et al , ). DKK1, in turn, is a secreted inhibitor of Wnt signaling (Fedi et al , ), and its overexpression decreases the invasive capability of melanoma cells in vitro (Chen et al , ) and increases apoptosis in melanoma cells in vitro and in vivo (Mikheev et al , ).…”
Section: Discussionmentioning
confidence: 99%